The effectiveness of "ILU" massage in infants as a complementary therapy reduce constipation in the Public Health Center: Keywords: Complementary,Massage "I L U", constipation - Sri Utami Subagio (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
Abstract Background: Giving MP-ASI is one of the supporting factors for growth and development, but nutritional intake is one of the factors that affect constipation. One alternative to the use of non-pharmacological therapy, which is administration to reduce constipation, is the "I L U" massage. Research methods : This research is a descriptive type of research, 5 babies who experience constipation were studied for 2 weeks using the bristol stool chart and Rome IV criteria instruments before and after giving the "I L U" massage. Results and Discussion : Babies who experience constipation are given "I L U" massage for 2 weeks with massage every 1 week 3 times which is observed based on the bristol stool chart and rome IV. Before the massage, the Bristol stool chart was 1-2 while Rome IV was 2-3 which indicates constipation. After 1 week after the massage, there was an increase in the Bristol stool chart and a decrease in Rome IV, and even 2 weeks after the â€œI L Uâ€ massage, the Bristol stool chart was 2,3,4 and Rome IV 0, indicating reduced constipation. Conclusion : There is an effect of giving "I L U" massage for 2 weeks on a decrease in the type of Bristol stool chart and a decrease in the value of Rome IV. Keywords: Complementary,Massage "I L U", constipation